Calcium-labile mitotic spindles isolated from sea urchin eggs (Lytechinus variegatus) (The Rockefeller University Press, 1980)
We isolated calcium-labile mitotic spindles from eggs of the sea urchin Lytechinus variegatus, using a low ionic strength, EGTA lysis buffer that contined 5.0 mM EGTA, 0.5 mM MgCl2, 10-50 mM PIPES, pH 6.8, with 1% Nonidet P-40 (detergent) and 20-25% glycerol. Isolated spindles were stored in EGTA buffer with 50% glycerol for 5-6 wk without deterioration. The isolated spindles were composed primarily of microtubules with the chromosomes attached. No membranes were seen. Isolated spindles, perfused with EGTA buffer to remove the detergent and glycerol, had essentially the same birefringent retardation (BR) as spindles in vivo at the same mitotic stage. Even in the absence of glycerol and exogenous tubulin, the isolated spindles were relatively stable in the EGTA buffer: BR decayed slowly to about half the initial value within 30-45 min. However, both the rate and extent of BR decay increased with concentrations of Ca2+ above 0.2-0.5 muM as assayed using Ca-EGTA buffers (0.2 mM EGTA, 0.5 mM MgCl2, 50 mM PIPES, pH 6.8, plus various amounts of CaCl2). Microtubules depolymerized almost completely in < 6 min at Ca2+ concentrations of 2 muM and within several seconds at 10 muM Ca2+. Of several divalent cations tested, only Sr2+ caused comparable changes in BR. The absence of membranes in the isolated spindles appeared to be associated with a lack of calcium- sequestering ability. Our results suggest that calcium ions play an important role in the depolymerization of spindle microtubules and that membrane components may function within the mitotic apparatus of living cells to sequester and release calcium ions during mitosis.